Performansi Keselamatan Kebakaran Penggunaan Aluminum Composite Panel (ACP) pada Bangunan Gedung - Ajun Hariono; Azhar Pangarso Laksono; Rahmandia Prasetia; Muhammad Firhand Agustio (Jurnal Permukiman, 2023)
ACP (aluminum composite panel) is commonly used as a building envelope coating system on the exterior of the building. ACP on the market generally has not been tested according to standards related to the level of fire resistance. There were many cases of fire spread in building fires in 2020 due to the use of ACP coating systems as building envelopes. The ACP to be studied is a Non-Fire Rated type ACP with the test method used are properties material test (non-combustibility test, ignitability test, fire spread test, and cone calori meter test) and intermediate scale test (refer to ISO 13785-1“Reaction to fire tests for facades - Intermediate-scale test”). Experiments conducted on three ACP constructions with PE (polyethylene) cores showed a unique flame propagation phenomenon. It can be visually seen that the fire propagates from the bottom directly to the top of the sample on the back side. It can be visually seen that the fire propagates from the bottom directly to the top of the sample on the back side. It can be seen that hot air flows upward through the gap formed between the ACP sheet and the wall where the sample is located. It is this chimney effect that allows the fire to propagate quickly from bottom to top. Based on the results of medium-scale fire tests, fire spread in ACP building housing systems can occur when polyethylene begins to burn and spread between panels. So that in its application, a way is needed so that as much as possible the PE core material is not easily exposed to fire or coated with Fire Retardant material and attention to its compartmentization.